A gene trap screen reveals the expression of the transcription factor Gfi1.1 in haemogenic endothelial cells of the Zebrafish embryo - Thambyrajah, Roshana Sutharshini (2012)
In vertebrates, haematopoiesis occurs in two waves. The primitive wave gives rise to transient myeloid and erythroid cells whereas the definitive wave generates haematopoietic stem cells (HSCs), which maintain the blood system throughout life. These HSCs are able to self-renew and to give rise to progenitors that differentiate into mature cells of all blood lineages. Little is known about the cellular origin and molecular programming of HSCs. This knowledge is useful to generate HSCs in vitro from embryonic stem cells or induced pluripotent cells. In zebrafish, HSCs form in the intermediate cell mass (ICM), in the trunk of the embryo. Here, they develop dorsal to the primitive red blood cells and in close association with the ventral wall of the dorsal aorta (DA). Like their mammalian counterparts, they express the transcription factors runx-1 and c-myb. As in other vertebrates, zebrafish HSCs are thought to arise from the haemogenic endothelium in the ventral wall of the DA. A signalling cascade that involves the Hedgehog, Vascular endothelial growth factor (Vegf) and Notch signalling pathways is needed for arterial specification of the DA and for HSC formation. Short-term lineage tracing experiments showed that cells in the ventral wall of the DA first seed the tail mesenchyme (caudal haematopoietic tissue, CHT) through blood circulation before they seed the final sites of haematopoiesis, the thymus and kidney in the adult fish. Here, we conducted a tol2-transposon based gene trap vector screen with eGFP as the reporter gene with the aim to label nascent HSCs in vivo and to identify novel genes involved in haematopoiesis. We obtained 174 transgenic lines with tissue-specific eGFP expression in non-haematopoietic and haematopoietic tissues. We identified two lines with marker gene expression in haematopoietic cells. One of the transgenic lines, I-551:eGFP, showed reporter gene expression in primitive red blood cells and in endothelial cells in the ventral wall of the DA at 25 hours post fertilization (hpf). Using inverse PCR we identified the trapped gene in I-551:eGFP as gfi1.1, the homolog of the mouse Growth independence factor 1 (Gfi1), a transcriptional repressor expressed in HSCs. Here, we present results that the transgenic line Gfi1.1:eGFP enables us to follow emerging haematopoietic progenitors from the ventral wall of the dorsal aorta in their subsequent migration to the CHT, before they seed the final haematopoietic sites, the kidney and thymus. We show that Gfi1.1:eGFP expression is restricted to the ventral wall of the dorsal aorta by combining the transgenic line with endothelial and aorta-specific transgenic lines. We further demonstrate that the endothelial expression of the eGFP in the aorta is dependent on the vegf and notch signalling pathway and co-localizes to cells which also express the transcription factors runx1 and c-myb. When Gfi1.1:eGFP embryos are injected with the runx1 morpholino (MO), gfi1.1 expression in haemogenic endothelial cells initially occurs, which indicates that initial gfi1.1 expression is independent of runx1. But a reduction in the number of eGFP positive cells is observed at 50 hpf in the CHT. Using time-lapse imaging, we were able to visualize gfi1.1 positive cells detaching from the haemogenic endothelium. This observation indicates that gfi1.1 positive cells in the CHT are derived from the haemogenic endothelium and therefore nascent HSCs. We therefore strongly suggest that this transgenic line labels haemogenic endothelial cells at 26hpf. The transgenic line Gfi1.1:eGFP therefore provides a tool for studying HSC development since its expression labels the emergence of nascent HSCs from haemogenic endothelial cells and continues to be expressed in larval and adult haematopoietic sites.